Multidomain Lifestyle Intervention Strategies for the Delay of Cognitive Impairment in Healthy Aging - Toman, Josef; Klímová, Blanka; Vališ, Martin (Nutrients, 2018)
Present demographic changes demonstrate that the number of elderly people is growing at a frenetic pace. This shift in population consequently results in many social and economic problems, which burden the social and economic systems of countries. The aging process is associated with age-related diseases, the most common of which are dementia and Alzheimer's disease, whose main symptom is a decline in cognitive function, especially memory loss. Unfortunately, it cannot be cured. Therefore, alternative approaches, which are cost-effective, safe, and easy to implement, are being sought in order to delay and prevent cognitive impairment. The purpose of this review was to explore the effect of multidomain lifestyle intervention strategies on the delay and/or prevention of cognitive impairment in healthy older individuals. The methods are based on a literature review of available sources found on the research topic in three acknowledged databases: Web of Science, Scopus, and PubMed. The results of the identified original studies reveal that multidomain lifestyle interventions generate significant effects. In addition, these interventions seem feasible, cost-effective, and engaging. Thus, there is a call for the implementation of effective lifestyle prevention programs, which would involve goal-setting and would focus on the prevention of crucial risk factors threatening the target group of elderly people, who are at risk of cognitive decline and dementia.
Keywords: rizikové faktory; životní styl; lidé; Life Style; cvičení; Risk Factors; Humans; Exercise; Healthy Aging; zdravé stárnutí